Floret Farm's discovering dahlias : a guide to growing and arranging magnificent blooms - Benzakein, Erin; Chai, Julie; Jorgensen, Jill (Chronicle Books, 2021)
"Grow and arrange breathtaking dahlias to enhance every occasion. In this luxe compendium, world-renowned flower farmer and floral designer Erin Benzakein reveals all the secrets to cultivating gorgeous dahlias. These coveted floral treasures come in a dazzling range of colors, sizes, and forms, with enough variety for virtually every garden space and personal preference, making them one of the most beloved flowers for arrangements. In these pages, readers will discover expert advice for planting, harvesting, and arranging garden-fresh dahlias, including a simple-to-follow overview of the dahlia classification system, an A-Z guide with photos and descriptions of more than 350 varieties, and step-by-step how-tos for designing show-stopping dahlia bouquets that elevate any occasion. Full of expert wisdom and overflowing with hundreds of lush photographs, DISCOVERING DAHLIAS is an essential resource for gardeners and a must-have for anyone who loves flowers"--